CORRELATION BETWEEN LENGTH OF SERVICE AND CHROMIUM LEVELS IN URINE OF WELDING WORKSHOP WORKERS - Arya Hafidh Fauzan; Isnin Aulia Ulfah Mu'awanah; Sri Martuti (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2026)
Welding is an industrial activity with a risk of exposure to hexavalent chromium (CrVI). Chromium levels are monitored through urine because the kidneys are the main route of excretion, so urine levels reflect the body's exposure levels. Specimens were collected through spontaneous urination in the morning using the midstream method. This study aimed to determine the relationship between work duration and urinary chromium levels in welding workshop workers. The study was conducted in seven welding workshops in four subdistricts in the Special Region of Yogyakarta using a cross-sectional design with an observational analytical approach. A total of 18 workers met the criteria as respondents. Morning urine samples were analyzed using graphite furnace atomic absorption spectrophotometry (GF-AAS) because the concentration is more concentrated and able to describe chromium accumulation. The analysis was performed descriptively and with Pearson's correlation test. The results showed no significant relationship between length of service and urinary chromium levels (p=0.078), although a moderate positive correlation was observed (r=0.427). The study concluded that length of service was not significantly related to urinary chromium levels. Further studies involving larger samples and considering confounding variables are recommended.